2021
DOI: 10.21121/eab.953538
|View full text |Cite
|
Sign up to set email alerts
|

Planned Obsolescence: Is It a Trap Set for the Consumer or Is It a Strategy Contributing to Social Development?

Abstract: Planned Obsolescence, which is a controversial concept with its positive and negative criticism in the literature, is a concept that refers to the limited life span of products. It attracts the attention of researchers that the concept is both identified with consumption culture and seen as an important development tool. Based on the question of "Is planned obsolescence a socioeconomic opportunity or a trap for consumers?" it is aimed to reveal the approaches of the experts in this study.Based on the qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, even if the product is subjected to the planned obsolescence strategy, it has been found that consumers feel satisfied with planned obsolescence when their wishes are fulfilled. The consumer is bored with using the product (Umar & Beyaz, 2021). However, this situation represents a psychological conflict situation in the inner world of the consumer.…”
Section: The Relationship Between Psychological Obsolescence and Sati...mentioning
confidence: 99%
See 3 more Smart Citations
“…However, even if the product is subjected to the planned obsolescence strategy, it has been found that consumers feel satisfied with planned obsolescence when their wishes are fulfilled. The consumer is bored with using the product (Umar & Beyaz, 2021). However, this situation represents a psychological conflict situation in the inner world of the consumer.…”
Section: The Relationship Between Psychological Obsolescence and Sati...mentioning
confidence: 99%
“…The planned obsolescence strategy is a discussed and controversial concept from both favorable and unfavorable perspectives (Umar & Beyaz, 2021). Some businesses can avoid planned obsolescence by producing highly durable products (Agrawal et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations